A survey on vision based techniques for detection and classification of fruit diseases - Kour, VipponPreet; Arora, Sakshi; Pal Singh, Jasvinder (International Journal of Engineering and Technology, 2018)
Indian economy depends heavily on its agriculture system. Horticulture sector has a major share in Indian agrarian economy. Therefore for agriculture industry to grow, the effective growth and improved yield of fruits is necessary. Diseased fruit production lays down various sensitive issues that can create various crises including reduced exports. To tackle such situations farmers need manual monitoring of fruits in all the development phases till harvest. But manual monitoring may not always give satisfactory results, owing to the subjective nature of the process. In order to reduce this stress, the technological support for such monitoring of fruit diseases was introduced. Image processing is one of the widely accepted areas for fruit disease detection and classification. With accurate disease diagnosis, the proper control actions can be taken at appropriate time. This paper is intended to aid in the analysis of various techniques and methodologies used in fruit disease detection so far.Â Â